Joss Whedon's Dollhouse and Joss Whedon's Dollhouse. - Rogers, Scott (Journal of the Fantastic in the Arts, 2011)
One of the most interesting features of the DVD releases of Joss Whedon's television series, Dollhouse, is the title: "Joss Whedon's Dollhouse." I argue that this full title has specific importance to our understanding of the series. The series was widely panned by critics, who tended to read it as a badly imagined attempt to explore identity by focusing its attention on beautiful people in tight-fitting clothes. This interpretation, I argue, missed Whedon's primary argument in Dollhouse, for if a dollhouse presupposes the existence of both dolls and those who play with them, the title of the series invites us to interpret it as a television show about television shows, their creators, and the institutions and economies in which they exist. When we consider Dollhouse within this framework, what emerges is a clear sense that in Dollhouse, Whedon used a television show to mount an argument about television shows—and the entertainment industry's failure to create and sustain television as an art form.